Ice-sheet Sourced Juxtaposed Turbidite Systems in Labrador Sea - Hesse, Reinhard; Klaucke, Ingo; Ryan, William; Piper, David (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary Ice-sheet sourced Pleistocene turbidite systems of the Labrador Sea are different from non-glacially influenced systems in their faciès distribution and depositional processes. Two large-scale sediment dispersal systems are juxtaposed,one mud-dominated and associated with the Northwest Atlantic Mid-Ocean Chan·net (NAMOC), the other sand-dominated and forming a huge submarine braided sand plain. Co-existence of the two systems reflects grain-size separation of the coarse and fine fractions on an enormous scale, caused by sediment winnowing at the entrance points of melt-water from the Laurentide Ice Sheet (LIS) to the sea (Hudson Strait, fiords) and involves a complex interplay of depositional and redepositional processes. The mud-rich NAMOC system is multi-sourced and represents a basinwide converging system of tributary canyons and channels. It focusses its sand load to the central trunk channel in basin centre, in the fashion of a "reverse" deep-sea fan.The sand plain received its sediment from the Hudson Strait by turbidity currents that were generated either by failure of glacial prodelta slopes at the ice margin, or by direct meltwater discharges with high bedload concentration. We speculate that the latter might have been related to subglacial-lake outburst flooding through the Hudson Strait, possibly associated with ice-rafting (Heinrich) events.